STRATEGI DIGITAL MARKETING DALAM MENJARING PESERTA DIDIK BARU - Zulhilmy Zulhilmy (Balai Diklat Keagamaan Bandung, 2023)
PPDB (New Student Admission) is a program that every educational institution possesses. Every educational institution, and particularly private educational institutions, competes for the attention of prospective students. Each educational institution has its own strategy for achieving predetermined goals. This study intends to characterize the digital marketing strategy utilized by MI Al-Muhajirien to recruit new students. This study aimed to determine how promotional strategies are utilized in the marketing of educational services. This research employs a qualitative-descriptive methodology. The condition of the research subject at the time of the research is based on its developmental stage. The subjects were school principals, assistant principals, educators, and educational employees. This study collects data through observation, documentation studies, and in-depth interviews. Throughout the research, descriptive qualitative data analysis and data triangulation techniques were used. According to the results of the conducted research, MI Al-Muhajirien's digital marketing on social media platforms and word-of-mouth promotion strategy can be implemented in accordance with the timetabled plan so that predetermined quotas are met